2016
DOI: 10.1007/s12016-016-8566-3
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Impairment in Rheumatoid Arthritis and Influence of Anti-TNFα Treatment

Abstract: There is evidence that rheumatoid arthritis (RA) is associated with higher overall and cardiovascular (CV) morbidity and mortality as compared with general population. Increased prevalence of traditional risk factors and chronic inflammation, that has been recognized as independent CV risk factor, may play an important role in atherosclerosis and subsequently ischemic heart disease development. However, myocardial dysfunction as a result of chronic inflammation and secondarily myocardial fibrosis markedly part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 85 publications
(110 reference statements)
2
9
0
Order By: Relevance
“…In addition, the results of regression analysis are also confirmed by the existence of the above relationships between RA and AS and morphological and functional changes of the heart in CMR in study group. The more frequent occurrence and greater severity of adverse cardiovascular changes in patients with RA in our study compared to the control group matches the results of other studies conducted so far, although most of them were conducted using echocardiography [18]. There are far fewer CMR studies.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the results of regression analysis are also confirmed by the existence of the above relationships between RA and AS and morphological and functional changes of the heart in CMR in study group. The more frequent occurrence and greater severity of adverse cardiovascular changes in patients with RA in our study compared to the control group matches the results of other studies conducted so far, although most of them were conducted using echocardiography [18]. There are far fewer CMR studies.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, research from our group has demonstrated a significant increase in collagen accumulation within the vastus lateralis, soleus and gastrocnemius muscles in CIA rodents compared to that of control rodents [38], as well as impaired molecular remodelling with fibrotic deposition and impaired cardiomyofibre contractile function [91]. In humans, the presence of subclinical myocardial fibrosis resulting from low grade chronic inflammation in a large number of RA patients, has been linked to heart failure in approximately 3.9% of patients [92]. Furthermore, pulmonary fibrosis is often associated with RA as a result of increased TGF-β and Smad signalling leading to an increase in collagen deposition within the lung tissue [93].…”
Section: Fibroblasts and The Extracellular Matrix (Ecm)mentioning
confidence: 80%
“… 44 Similarly, in the Tg197 model, valvular pathology contributes to the observed extensive LV dilation with some degree of LV hypertrophy as well as to the concomitant contractile dysfunction. However, additional mechanisms that have been proposed as contributing factors in the increased prevalence of global heart failure in patients with RA/SpA, such as myocardial fibrosis and oedema as well as arterial blood pressure, coronary heart disease and myocardial remodeling 45 remain to be studied for their contribution in the global heart impairment observed in Tg197 animals. We have also detected repeated arrhythmic episodes in Tg197 mice which could explain the premature sudden deaths observed in this model recapitulating the increased risk of sudden cardiac death experienced by patients with RA/SpA, due to atrial fibrillation and other types of tachyarrhythmias which suggest diffuse myocardial electrical instability.…”
Section: Discussionmentioning
confidence: 99%